Disruption of the Formation of Civic Morality through the Implementation of the Pancasila Student Profile in Elementary Schools - Khaidir Fadil; Sintha Sih Dewanti; Ibrahim; Abroto; Noor Isna Alfaien; Muhammad Fahri; Ayunda Rahma (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Pancasila, as the ideological foundation of the nation, plays a central role in shaping the character of the younger generation. However, in practice, the implementation of Pancasila values through the Pancasila Student Profile Strengthening policy still faces serious challenges, especially in the context of shaping students' civic morality. This study aims to identify the obstacles and inconsistencies in the implementation of this policy, while also examining effective strategies for strengthening character based on Pancasila. This study uses a qualitative approach with a literature review method, systematically reviewing 60 articles indexed in SINTA and SCOPUS over the past five years. Data analysis refers to the Miles & Huberman model through the stages of data collection, data reduction, data presentation, and verification. The results of the study reveal three main obstacles: low teacher understanding of the implementation of Pancasila values, lack of supporting training, and insufficient integration of values into the school curriculum. Conversely, contextual learning based on local values and the role of teachers as facilitators of values have proven effective in strengthening students' civic morality. This study concludes that strengthening the Pancasila Student Profile must be done collaboratively, reflectively, and contextually to optimize the internalization of Pancasila values. The implications of this research contribute theoretically and practically to the development of more applicable character education policies in school environments.